Faktor Yang Mempengaruhi Struktur Modal Perusahaan Aneka Industri Yang Terdaftar Di BEI - Tamara Christhalia, Jonardi (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
The purpose of this empirical research is to obtain empirical evidence about the influence of profitability, liquidity, and asset growth on the capital structure. As of the purposes to determine the effect of asset growth was moderated by interest rate on the capital structure on company listed on the stock exchange from 2013-2017. This research uses data varias industries that were selected using purposive sampling method for a total of 150 data in five years. The data used in this research are secondary data in the form of financial statements. The results show that profitability and asset growth moderated by interest rate affect to capital structure, whereas liquidity and asset growth does not affect to capital structure. Simultaneously, the testing shows independent variable have a significant impact on the capital structure. Testing results show that the coefficient of determination before moderated of 77.83% dependen variable is affected by the independent variable, while the remaining 22.17% is explained by other variables. Testing results show that the coefficient of determination after moderated increase of 0.63% to be 77.83%